El inicio en los negocios del «Clan de Tarancón» en España (1833-1850) - Cristina Bienvenida Martínez García (Cuadernos de Ilustración y Romanticismo)
The marriage of Fernando Muñoz, Corps guard, with María Cristina de Borbón, allowed him to organize a power group in the Court (which I call the "clan of Tarancón"), using the influence of the Royal Household and the income that was allocated to the royal family for its economic and social advancement. The scholars of Spanish Contemporary History have not paid attention to the importance that the Royal House still enjoyed within the organization of the State. Muñoz knew how to use this influence to control politics and to insert himself into the most important economic circles of the nation. In this article I study how this process was initiated.